1978
DOI: 10.1007/bf01906527
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and myocardial effects of long-lasting venodilation in the conscious dog

Abstract: The effect of molsidomine-induced venodilation on cardiac preload was studied in conscious resting dogs, instrumented to analyze left ventricular function and myocardial perfusion. Direct effects on veins were studied during chloralose anesthesia by measuring regional venous capacitance changes with an induction angiometer. Kinetics of molsidomine-induced effects were compared to those induced by nitroglycerin and isosorbide dinitrate. This comparison was restricted to low i.v. dosages, causing only transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 23 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…This decline causes lowered myocardial oxygen demands due to lowered myocardial wall tension and, additionally, improves the conditions for myocardial perfusion by lowering the extravaseular coronary resistance (22). This therapeutically favourable effect on cardiac preload results from the vasodilatory action of molsidomine, which does not involve dilating influences on total peripheral resistance or coronary resistance vessels (15,29). The dilation in the vessels of the low pressure system can be described quantitatively by the analysis of the effective compliance of the total vascular bed, thus allowing repeated studies in conscious animals on the effect of chronic venodilation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This decline causes lowered myocardial oxygen demands due to lowered myocardial wall tension and, additionally, improves the conditions for myocardial perfusion by lowering the extravaseular coronary resistance (22). This therapeutically favourable effect on cardiac preload results from the vasodilatory action of molsidomine, which does not involve dilating influences on total peripheral resistance or coronary resistance vessels (15,29). The dilation in the vessels of the low pressure system can be described quantitatively by the analysis of the effective compliance of the total vascular bed, thus allowing repeated studies in conscious animals on the effect of chronic venodilation.…”
Section: Discussionmentioning
confidence: 97%
“…Animal experiments (8,11,15,29) and clinical studies (5,19,20,(25)(26)(27) demonstrated that the reduction of intramyocardial wall tension due to lowered preload is the main therapeutic principle of the drug. Because of the documented long duration of its antianginal and venodilating action molsidomine may be a promising candidate for pharmacological prophylaxis of anginal attacks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These doses are higher than those needed to evolve venous pooling and to reduce cardiac preload by reducing the cardiac filling pressure. In animal experiments, approximately 0.5 g/kg molsidomine is necessary to observe significant effects on peripheral resistance [21]. Only then can a decrease in the arterial pressure be demonstrated that exceeds the concomitant reduction in cardiac output.…”
Section: Sin-1 Dose-response Changes In Hemodynamic Resistive and mentioning
confidence: 97%
“…It seemed therefore of importance to clarify whether molsidomine, another long-acting vasodilator with a peripheral site of action similar to ISDN (14), would elicit counterregulatory mechanisms. Molsidomine exerts its antianginal effect via lowering of the venous return by dilation of the capacitance vessels, leading to diminished ventricular volume, a decrease in cardiac output and, hence, a decrease in myocardial oxygen consumption (2,8,14,9). *) A preliminary report of this study has been presented at the 21st Spring Meeting of the Deutsche Pharmakologisehe Gesellschaft (Naunyn-Schmiedeberg's Arch.…”
Section: Introductionmentioning
confidence: 99%